2022
DOI: 10.3390/ijerph192417007
|View full text |Cite
|
Sign up to set email alerts
|

Ableism, Human Rights, and the COVID-19 Pandemic: Healthcare-Related Barriers Experienced by Deaf People in Aotearoa New Zealand

Abstract: The COVID-19 pandemic significantly affected global healthcare access and exacerbated pre-pandemic structural barriers. Literature on disabled people’s experiences accessing healthcare is limited, with even less framing healthcare access as a human rights issue. This study documents and critically analyses Deaf people’s healthcare access experiences in Aotearoa New Zealand during the COVID-19 pandemic. Eleven self-identified Deaf individuals participated in semi-structured videoconferencing interviews. Discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Effective communication is core to truly embedding person-centered care into practice [ 38 ]. Our findings concerning hearing impairment mirror those of earlier research into Deaf people’s experiences of health care access over the pandemic in New Zealand [ 39 ]. While research into telehealth has largely suggested the equivalence of this delivery method, telehealth could allow some clients to be underserved, specifically, those who are less proficient at verbalizing their distress; this could also affect a client’s willingness to use telehealth.…”
Section: Discussionsupporting
confidence: 84%
“…Effective communication is core to truly embedding person-centered care into practice [ 38 ]. Our findings concerning hearing impairment mirror those of earlier research into Deaf people’s experiences of health care access over the pandemic in New Zealand [ 39 ]. While research into telehealth has largely suggested the equivalence of this delivery method, telehealth could allow some clients to be underserved, specifically, those who are less proficient at verbalizing their distress; this could also affect a client’s willingness to use telehealth.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings affirm that disabled New Zealanders' access to healthcare and disability support services were negatively impacted by the pandemic, consistent with extant literature [8,11,13,[21][22][23]. Our study has revealed that, while policy decisions generally negatively impacted the healthcare and disability support of disabled individuals, some policies resulted in positive outcomes for disabled people.…”
Section: Discussionsupporting
confidence: 90%
“…However, the ongoing restrictions also significantly disrupted healthcare and support services, resulting in challenges for disabled people. For example, staff shortages were exacerbated by infection control measures, staff illness, and mandatory self-isolation periods, resulting in in-home support services being scaled back, disrupted, or even suspended, and many community services, such as day programmes and respite care were also negatively impacted [11][12][13].…”
Section: The New Zealand Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, takatāpui who are gender diverse, and trans people and whānau who are also part of other underserved communities may navigate intersecting and compounding barriers to accessing healthcare. These barriers include the impacts of colonisation and racism (Espiner et al, 2021) and ableism (Roguski et al, 2022), alongside hetero-and cisnormativity in health systems (Pihama, 2020).…”
Section: Raising Knowledge and Awarenessmentioning
confidence: 99%